(untitled) (Scientific electronic journal "Labor Economics and Human Capital", 2023)
This article highlights the possibilities of increasing the employment of the population in the field of entrepreneurship with the effectiveness of investments in the Jizzakh region. By this, the possibilities of increasing the employment of the population in the field of entrepreneurship, the efficiency of investments, the possibilities of development in the Jizzakh region on the basis of sectors are presented.